Feeding Behavior of Tonkean Macaques (Macaca tonkeana) in Schmutzer Primates Center and Ragunan Zoo, Jakarta - Riptianingsih, Fery Dwi; Farajallah, Dyah Perwitasari; Astuti, Dewi Apri (UI Scholars Hub, 2015)
Tonkean macaques are one of seven endemic macaque species on Sulawesi Island. Feeding management in captivity should pay attention to the quality, palatability, and feeding behavior patterns of animals. The goal of this study was to compare the feeding behavior of two social groups of Tonkean macaques at Schmutzer Primates Center (SPC) and Ragunan Zoo (RZ) with different captive management, which was expected to affect feeding behavior. Ad libitum sampling was used to observe daily behavior and hierarchy, while focal animal sampling was used to observe feeding behavior and feed preference. Data were collected from September 2013 until March 2014 with a total of 495 hours of observations. There were significant differences between the daily behavior of two groups of Tonkean macaques. Resting behavior was dominant in RZ group with non-enrichment feed cage, while feeding behavior was more common in the SPC group with an enrichment feed cage. The SPC group spent most of their feeding time in searching for feed, while choosing, carrying and refusing were greater in the RZ group. Both Tonkean macaque groups showed individual dominance in their feeding behavior. Provisioned feed in both locations had different diversity and preference values. The selection of feed required was based on preference values with attention to Tonkean macaques’ feed in nature. Cage construction, such as the SPC cage, was able to reduce abnormal behavior exhibited by individuals.